Smart Zigbee/IEEE 802.15.4 MAC for wireless sensor multi-hop mesh networks - Shabani, Hikma; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A.; Habaebi, Mohamed Hadi (2013)
The future of Smart Grid is based on grid-integrated real-time communications between the grid elements of generation, transmission, distribution and loads. Due to Zigbee/IEEE 802.15.4 standard’s features such as low cost, low power, low data rate, short range, simplicity and free licensed spectrum which makes Zigbeebased wireless sensor networks (WSNs) the wireless technology of choice for smart grid applications. This paper focuses on the electricity distribution layer, ranging from Advanced Metering Infrastructure (AMI) gateways at the house-hold to the distribution point where a multi-hop mesh network is built for large coverage data exchanges. Although beacon-based mode of operation is adopted in IEEE802.15.4 standard, it does not, however, specify any mechanism to enable beacon mode in mesh networks. Therefore, in this paper, the Zigbee/IEEE 802.15.4 MAC protocol is modified to suit the beacon-based wireless sensor multi-hop mesh networks application. Such network configuration is expected to proliferate in is smart grid auto-metering scenarios. A simulation model was built and validated using the network simulator (NS-2) and the preliminary results showed considerable enhancements as expected for the ZigBee/IEEE 802.15.4 MAC protocol.